AN ALGORITHM FOR GENERATING SINGLE DIMENSIONAL FUZZY ASSOCIATION RULE MINING - Intan, Rolly (Institute of Research and Community Outreach - Petra Christian University, 2006)
Association rule mining searches for interesting relationship among items in a large data set. Market basket analysis, a typical example of association rule mining, analyzes buying habit of customers by finding association between the different items that customers put in their shopping cart (basket). Apriori algorithm is an influential algorithm for mining frequent itemset for generating association rules. For some reasons, Apriori algorithm is not based on human intuitive. To provide a more human-based concept, this paper proposes an alternative algorithm for generating the association rule by utilizing fuzzy sets in the market basket analysis.